Characterization of composite materials (Momentum Press, 2010)
Development of new materials is becoming increasingly difficult, both because of increased environmental concerns and because the number of useful materials made from simple components is limited. We are thus motivated to focus our attention on the improved use of existing materials. Composite materials are ideal candidates for this purpose. Composite materials can be narrowly defined to be fiber-reinforced polymers, such as carbon fiber-reinforced epoxy resin. However, as composite technology has advanced, the definition of composite materials has become broader, to include materials such as molecular composites and nanocomposites which are also similar to immiscible blends. From a characterization perspective, these materials can be treated as heterogeneous materials. While all characterization techniques can be used for homogeneous materials, the subject discussed in this volume emphasizes the unique features of composite characterization.